2007
DOI: 10.1007/s10552-007-9022-8
|View full text |Cite
|
Sign up to set email alerts
|

Youth smokers’ beliefs about different cessation approaches: are we providing cessation interventions they never intend to use?

Abstract: Findings have the potential for informing the development of more effective campaigns for engaging adolescent smokers into smoking cessation treatment. Results also reinforce the need for programmatic innovation within and beyond school settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Although higher dependence was associated with somewhat lower confidence, it is nonetheless likely that youths underestimate both the difficulties of quitting and their levels of nicotine dependence, believing that they are able to independently quit when they wish. Of note, participants were largely uninterested in attending smoking cessation programs or even receiving information about smoking, also consistent with other research (e.g., Leatherdale & McDonald, 2007). Unfortunately, this represents a significant barrier to successful quitting; behavioral smoking cessation programs increase a young person's chance of quitting (e.g., Currey et al, 2009;DeHay et al, 2012).…”
Section: Smoking Cessationsupporting
confidence: 77%
“…Although higher dependence was associated with somewhat lower confidence, it is nonetheless likely that youths underestimate both the difficulties of quitting and their levels of nicotine dependence, believing that they are able to independently quit when they wish. Of note, participants were largely uninterested in attending smoking cessation programs or even receiving information about smoking, also consistent with other research (e.g., Leatherdale & McDonald, 2007). Unfortunately, this represents a significant barrier to successful quitting; behavioral smoking cessation programs increase a young person's chance of quitting (e.g., Currey et al, 2009;DeHay et al, 2012).…”
Section: Smoking Cessationsupporting
confidence: 77%
“…Only a very small proportion of former smokers reported a successful cessation (3% of regular and 16% of occasional smokers). Adolescents’ negative attitudes towards smoking cessation programs have been documented [12]. It appears that young people feel confident that they can stop smoking without assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the low interest in participating in smoking cessation programs has been reported [12], little attention has been paid to the development of effective recruitment methods for adolescents [7]. In fact, most adolescents who successfully quit smoking report that they quit on their own or with the help of a friend [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies indicate that recruitment is also a challenge in adolescent smoking cessation. For instance, Leatherdale et al [6, 7] found that 77% of Canadian adolescents planning to quit preferred to quit on their own and that Canadian youth has a rather negative perception about formalized smoking cessation interventions. Backinger et al [8] estimated that recruitment rates in adolescent smoking cessation are between 2 and 10%.…”
Section: Introductionmentioning
confidence: 99%